Requirements for achieving economic sustainability of strategic extractive projects and their role in promoting local development - FERDJI, Mohamed; ZIDAN, Lakhdar; BENSAID, Lakhdar (The International tax journal, 2026)
This study aims to highlight the role of strategic extractive projects in promoting local development in remote areas, while examining the requirements for achieving the sustainability of these projects. It addresses the issue of the extent to which extractive investments contribute to sustainable development, with a particular focus on its economic dimension. The study puts forward the hypothesis that achieving such development is possible if these projects are accompanied by economic diversification strategies and investment in human capital. This study adopts a descriptive approach through the review of a wide range of previous studies addressing this topic, along with an analysis of selected international experiences such as Norway, Botswana, Malaysia, Venezuela, and South Africa. The findings reveal that countries which have relied on good governance, institutional independence, financial transparency, as well as the adoption of economic diversification policies and the establishment of sovereign wealth funds, have succeeded in achieving economic, social, and environmental sustainability.